POLIGAMI DALAM PERSPEKTIF AL-QUR`AN - Isti'anah, Isti'anah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
The practice of polygamy has existed long before Islam and has become a permissible custom. Unfortunately, many people assume that polygamy is a practice that was only known after the arrival of Islam. Ironically, Islam is considered to monopolize and legalize polygamy. In reality, Islam came by providing restrictions on polygamous marriages with certain limitations. Justice in polygamy is an obligation that must receive special attention, because the word "fair" is very easy to say but difficult to implement. In this study, the author focuses on the verses of the Qur'an related to polygamy, namely; Surah An-Nisa' verse 3. This type of research is entirely library research taking data from literature related to the research theme. The analysis technique in this writing uses a content analysis model by exploring and analyzing the thoughts or views of scholars on the verses of the Qur'an related to polygamy.